2016
DOI: 10.1039/c6ra18487a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of TiO2 nanoparticles in Nitzschia palea to form diatom nanotubes: an ingredient for solar cells to produce electricity and biofuel

Abstract: Diatoms are nature's nanobot because they can be described as cells in a glass house.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…An interesting study recently reported by Gautam et al shows that the metabolic incorporation of titania nanoparticles into Nitschia palea living diatoms induces the formation of TiO 2 nanotubes that are specifically located inside the frustule pores . Isolated titania‐nanotube‐doped frustules were used as a coating substrate for photoanodes in DSSCs and almost double (9.45% vs 4.20%) power efficiency was recorded versus a reference device using TiO 2 instead of the metabolically modified diatom shells.…”
Section: In Vivo Modification Of Biosilica Shellsmentioning
confidence: 97%
“…An interesting study recently reported by Gautam et al shows that the metabolic incorporation of titania nanoparticles into Nitschia palea living diatoms induces the formation of TiO 2 nanotubes that are specifically located inside the frustule pores . Isolated titania‐nanotube‐doped frustules were used as a coating substrate for photoanodes in DSSCs and almost double (9.45% vs 4.20%) power efficiency was recorded versus a reference device using TiO 2 instead of the metabolically modified diatom shells.…”
Section: In Vivo Modification Of Biosilica Shellsmentioning
confidence: 97%
“…Furthermore, the similarity of these structures to artificial photonic crystals led to the study of their ability to manipulate light 14 19 . Potential exploitation of optical, mechanical and structural properties of diatom frustules has been predicted and tested in several fields: design and development of highly efficient solar cells 20 22 ; plasmonics and Surface Enhanced Raman Spectroscopy (SERS) 23 25 ; sub-diffractive optics 26 ; photoluminescence-based sensors and biosensors 27 , 28 ; molding in micro- and nano- devices fabrication 29 ; nanovectoring of therapeutic agents in cancer cells 30 , 31 ; random lasing and dye trapping 32 , 33 , with several further innovative applications repeatedly envisaged 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this study tyrosine and tyrosine‐Zn II conjugates were incubated with diatom Nitzschia palea, which was cultured as per the standard lab procedure in a modified f/2 media . The cultured diatoms were sonicated and washed as described in published literature and used for the fabrication . The analysis of co‐incubated samples of Nitzschia palea with tyrosine and tyrosine‐Zn II conjugate revealed that deposition of tyrosine (Figure B&B’) and tyrosine‐ Zn II (Figure C&C’) over the surface ofdiatoms when analyzed under low vacuum SEM.…”
Section: Figurementioning
confidence: 78%